2009
DOI: 10.1002/pros.21075
|View full text |Cite
|
Sign up to set email alerts
|

The expression of osteoclastogenesis‐associated factors and osteoblast response to osteolytic prostate cancer cells

Abstract: Background-Prostate cancer (PCa) has a propensity to metastasize to bone. Tumor cells replace bone marrow and can elicit an osteoblastic, osteolytic, or mixed bone response. Our objective was to elucidate the mechanisms and key factors involved in promoting osteoclastogenesis in PCa bone metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 25 publications
2
33
0
Order By: Relevance
“…These analyses indicated that under identical conditions, the newer version of the antibody does not stain tumor cells in bone metastases, yet, the older antibody batch gave similar results to that reported previously (15) with strong tumor cell staining (C. Morrissey, unpublished data). Taken together with the present study, it would appear that prior results showing high level expression in tumor cells is related to antibody lot variability and it no longer appears with the newer currently available antibody from the same vendor.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…These analyses indicated that under identical conditions, the newer version of the antibody does not stain tumor cells in bone metastases, yet, the older antibody batch gave similar results to that reported previously (15) with strong tumor cell staining (C. Morrissey, unpublished data). Taken together with the present study, it would appear that prior results showing high level expression in tumor cells is related to antibody lot variability and it no longer appears with the newer currently available antibody from the same vendor.…”
Section: Discussionsupporting
confidence: 80%
“…Likewise, a previous study using IHC to detect IL6 production in prostate cancer metastases reported over twice as many bone metastases samples are positive for IL6 than soft tissue metastases, and with much stronger staining intensity (15). Unfortunately, our data do not support those results.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations